2008
DOI: 10.1115/1.2777186
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling Effectiveness Distributions on a Turbine Blade Cascade Platform With Stator-Rotor Purge and Discrete Film Hole Flows

Abstract: An experimental investigation to obtain detailed film cooling effectiveness distributions on a cooled turbine blade platform within a linear cascade has been completed. The Reynolds number of the freestream flow is 3.1×105, and the platform has a labyrinthlike seal upstream of the blades to model a realistic stator-rotor seal configuration. An additional coolant is supplied to the downstream half of the platform via discrete film cooling holes. The coolant flow rate through the upstream seal varies from 0.5% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Using coolant (at 0.5% to 2% of mainstream passage mass flow rate) with DR = 1.0, it was concluded that using typical advanced rotor-stator seals reduces film cooling effectiveness compared with conventional inclined slots. Wright et al (2008) used discrete film cooling holes in addition to the inclined slots to improve film coverage. Wright et al (2009) tested the effect of upstream wakes generated by wake rods and delta wings to simulate the effect of upstream stator wakes and end-wall vortices, with the conclusion that the delta wings produce a larger negative effect on film cooling.…”
Section: Endwallmentioning
confidence: 99%
“…Using coolant (at 0.5% to 2% of mainstream passage mass flow rate) with DR = 1.0, it was concluded that using typical advanced rotor-stator seals reduces film cooling effectiveness compared with conventional inclined slots. Wright et al (2008) used discrete film cooling holes in addition to the inclined slots to improve film coverage. Wright et al (2009) tested the effect of upstream wakes generated by wake rods and delta wings to simulate the effect of upstream stator wakes and end-wall vortices, with the conclusion that the delta wings produce a larger negative effect on film cooling.…”
Section: Endwallmentioning
confidence: 99%
“…The results indicated the existence of a strong interference between the cooling jets and the endwall secondary flows. PSP technique was also used by Wright et al [20] cooling effectiveness distributions on a blade platform with both purge flow and discrete film holes. Takeishi et al [21] investigated the influence of film cooling jet on leading edge horseshoe vortex employing LIF, PIV techniques.…”
Section: Introductionmentioning
confidence: 98%
“…The results indicated the existence of a strong interference between the cooling jets and the endwall secondary flows. PSP technique was also used by Wright et al [20] to study the film cooling effectiveness distributions on a blade platform with both purge flow and discrete film holes. Takeishi et al [21] investigated the influence of film cooling jet on leading edge horseshoe vortex employing LIF, PIV techniques.…”
Section: Introductionmentioning
confidence: 99%